Adoption Of Dewi Manggung Management Innovation (Case Study Of South Subang Tourism Village) - SUPANDI, Supandi; RONDA, Mirza; SIGIT, Ridzki Rinanto (International Journal of Environmental, Sustainability, and Social Science, 2023)
The research aims to plan the management outreach process to the community regarding developing a tourist village in South Subang. Including finding patterns of acceptance and suitability of the idea of developing a tourist village in South Subang, as well as finding and identifying the factors that influence community acceptance of the idea of developing a tourism village in South Subang. The results of the research using quantitative data and reinforced with qualitative data indicate that the process of socializing management to the community is carried out persuasively and recognizes the characteristics of the village community who are the target of communication. While the community accepts the idea of developing a tourist village in South Subang, some support it, and some are unhappy. Therefore, the factors that affect the acceptance of village communities to the idea of developing a tourist village in South Subang can involve opinion leaders, namely community leaders or leaders who are respected and combined with adopting Innovation. This strengthens the theory (Festinger, 1957) of social psychology and Lazarsfeld regarding opinion leaders combined with the concept of Innovation (Rogers, 2003).